2013
DOI: 10.1002/elan.201300303
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gold Nanoparticle Film Porosity on the Chemiresistive Sensing Performance

Abstract: The porosity of 1-hexanethiol-functionalised gold nanoparticle films was assessed and utilised as chemiresistor sensors. Electrochemical capacitance measurements showed that the accessibility of electrolytes of different ionic strengths into the pores depended on the thickness of the electric double layer formed. A large variation in capacitance was measured in 0.01-1000 mM NaClO 4 , implying a wide pore size distribution. The change in morphology of the nanoparticle films upon storage in air, water and ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…7,36 Indeed, several studies indicated their inuence on the sensing properties. [37][38][39][40] For example, assemblies of thiol-stabilized cubic platinum nanoparticles, revealing a more compact structure than their spherical counterparts, showed considerably higher response amplitudes. 38 Further, the perforation of assemblies of thiol-stabilized GNPs has been shown to markedly alter the chemiresistive response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,36 Indeed, several studies indicated their inuence on the sensing properties. [37][38][39][40] For example, assemblies of thiol-stabilized cubic platinum nanoparticles, revealing a more compact structure than their spherical counterparts, showed considerably higher response amplitudes. 38 Further, the perforation of assemblies of thiol-stabilized GNPs has been shown to markedly alter the chemiresistive response.…”
Section: Introductionmentioning
confidence: 99%
“…39 For chemiresistive sensing in liquid phase using an assembly of thiol-stabilized GNPs it has been shown that reducing the number of cavities with diameters between 0.3 to 3 nm signicantly prolongs the response time and at the same time increases the response amplitudes. 40 The cavity sizes in that study were estimated using electrochemical capacitance measurements. A more widely used technique to study cavity sizes of nanoporous materials, such as zeolites, are gas adsorption (BET-) measurements.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] Our group has expanded the potential utility of gold nanoparticle fi lms by showing that electrical resistance modulation can also occur in aqueous electrolyte solution. [ 4,[12][13][14][15][16][17][18] Following this, Lai et al [ 19 ] have shown that proteins can also modulate the resistance in biological samples. However, in all these cases, modulation of the nanoparticle fi lm resistance occurred via passive partitioning of a chemical species.…”
mentioning
confidence: 93%
“…When the organic chemical species is positively charged, e.g. [ 4,[12][13][14][15][16][17][18] Following this, Lai et al [ 19 ] have shown that proteins can also modulate the resistance in biological samples. The positive gate voltage induces negative charges inside the nanoparticles which drives the positively charged ions (cetyl pyridinium) into the fi lm where the organic component of the species is believed to intercalate with the hexanethiolate coating and thereby increase the interparticle separation.…”
mentioning
confidence: 99%
See 1 more Smart Citation